1994
DOI: 10.1128/mcb.14.2.1347
|View full text |Cite
|
Sign up to set email alerts
|

Polypurine sequences within a downstream exon function as a splicing enhancer.

Abstract: We have previously shown that a purine-rich sequence located within exon M2 of the mouse immunoglobulin gene functions as a splicing enhancer, as judged by its ability to stimulate splicing of a distant upstream intron. This sequence element has been designated ERS (exon recognition sequence). In this study, we investigated the stimulatory effects of various ERS-like sequences, using the in vitro splicing system with HeLa cell nuclear extracts. Here (la, 9, 13, 34) or the secondary structure of the region a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
216
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(225 citation statements)
references
References 49 publications
8
216
1
Order By: Relevance
“…In vitro splicing assays have shown that deletions or substitutions of the (GAR) n repeats found in ASLV, IgM, and related ESEs diminish or abolish their ability to promote splicing of an upstream intron (Katz and Skalka 1990;Fu et al 1991;Watakabe et al 1993;Xu et al 1993;Dirksen et al 1994;Tanaka et al 1994). To assess the dependence of ESE activity in S. pombe upon the purine-rich repeats, we constructed two mutant versions of the ASLV ESE located downstream from the 3Ј-splice site in the cdc2-I2 9R minigene (Fig.…”
Section: Ese Activity In Fission Yeast Displays Sequence and Spacing mentioning
confidence: 99%
“…In vitro splicing assays have shown that deletions or substitutions of the (GAR) n repeats found in ASLV, IgM, and related ESEs diminish or abolish their ability to promote splicing of an upstream intron (Katz and Skalka 1990;Fu et al 1991;Watakabe et al 1993;Xu et al 1993;Dirksen et al 1994;Tanaka et al 1994). To assess the dependence of ESE activity in S. pombe upon the purine-rich repeats, we constructed two mutant versions of the ASLV ESE located downstream from the 3Ј-splice site in the cdc2-I2 9R minigene (Fig.…”
Section: Ese Activity In Fission Yeast Displays Sequence and Spacing mentioning
confidence: 99%
“…The (ras)IDX contains no (GAR) n repeats in its sequence. Therefore, the ESE sequence of the ASLV (Tanaka et al, 1994) was added to the (ras)IDX, 50 nt away from its 3'SS, in order to determine whether this sequence could activate trans-splicing of the (ras)IDX. This molecule was named N pre-mRNA.…”
Section: The (Ras)idx Acceptor Does Not Trans-splice With Other Hetermentioning
confidence: 99%
“…For (M) plasmid L was linearized with PstI and transcribed with T7 RNA polymerase. For (N) the avian sarcoma-leukosis virus (ASLV) enhancer was obtained from pSP72-ASLV (env 3' exon) (Tanaka et al, 1994) that had been cut with XbaI and HindIII, and the fragment was subcloned in Bluescript SK (7) plasmid that had itself previously been cut with XbaI and HindIII. This plasmid, named pre-ASLV, was ®nally cut with XbaI.…”
Section: Pre-mrnasmentioning
confidence: 99%
“…Exonic splicing enhancers are sequences, found in certain exons, that can stimulate spliceosome assembly at the upstream 3' splice site of the exon (Fu et al 1991;Lavigueur et al 1993;Sun et al 1993;Watakabe et al 1993;Caputi et al 1994;Dirksen et al 1994;Staknis and Reed 1994;Tanaka et al 1994;Tian and Maniatis 1994;Ramchatesingh et al 1995;Wang et al 1995). Exonic enhancers are usually purine-rich sequences whose ac-…”
mentioning
confidence: 99%